Optical Coherence Tomography Findings in Cannabis Users - YORGUNER, NEŞE (TURKIYE SINIR VE RUH SAGLIGI DERNEGI, 2020)
Objective: In this study, we aimed to evaluate the effects of cannabis use on the retinal nerve fiber layer (RNFL) and the macular ganglion cell - inner plexiform layer GCL-IPL using optical coherence tomography (OCT). Method: This prospective, comparative study included 26 cannabis users who were evaluated at the Psychiatry Outpatient Unit of Mus State Hospital and 27 age and gender matched healthy controls. OCT was performed on both groups. The RNFL and GCL - IPL thicknesses, measured automatically by OCT, were recorded and compared between the groups. Results: The sociodemographic parameters of the two groups did not differ. The mean retinal nerve fiber thickness and thickness at the superior, nasal, inferior quadrants were not significantly different; but there was a significant difference at the temporal quadrant (p=0,022). In the analysis of macular ganglion cell - inner plexiform layer, the mean values as well as the infetotemporal, inferior, inferonasal and superonasal quadrants did not show significant differences. But there was a statistically significant decrease in the superior and superotemporal quadrants (p=0,006, p=0,027). Conclusion: These findings suggest that cannabis use leads to the thinning on retinal layers. As it is an easily observable part of the brain, evaluating retinal nerve fiber and ganglion cell layer with OCT may be important for monitoring toxic and degenerative effects in cannabis users.
Keywords: Optical coherence; cannabis; retinal nerve fiber; FIBER LAYER THICKNESS; GANGLION-CELL LAYER; SCHIZOPHRENIA; PATTERN